Review of Recent Patents on Vertical-Axis Wind Turbines (VAWTs) - Zoucha, Jack; Crespo, Cristina; Wolf, Hanna; Aboy, Mateo (Recent Patents on Engineering, 2023)
Background: Vertical axis wind turbines (VAWTs) provide an opportunity to take advantage of wind power in a variety of places unfit for traditional horizontal axis wind turbines (HAWT). Despite suffering from a lower efficiency in ideal conditions, other key advantages of vertical axis turbines still give them the ability to outperform traditional wind turbines, especially in urban, low-wind, and turbulent areas around the world. Objective: The purpose of this paper was to conduct a state-of-the-art patent search to analyze recent technological advancements in VAWT designs and deliver an overview of significant patents within this particular field of technology. Methods: An extensive patent search was performed to determine patents issued in the United States pertaining to the design innovation of VAWTs. The research implements an empirical approach to inspect patent information and qualitative analysis of the appropriate patents published in VAWT technology. Results: The patent search returned 506 total patents with almost 64% of advancements made in the past ten years, but with limited advancements made within the last 5 years. This article reviews sixteen patent publications since 2010 that highlight the most distinctive VAWT designs. Conclusion: Although progress has stalled over the last 5 years, VAWTs remain a plausible solution for many different environments and non-traditional implementations. While HAWTs have proved to be more efficient, the versatility of reviewed VAWT designs creates a new and untapped potential for wind as a renewable energy source.
Keywords: windmill